2013
DOI: 10.1152/japplphysiol.01455.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lung membrane conductance and capillary volume derived from the NO and CO transfer in high-altitude newcomers

Abstract: Acute exposure to high altitude may induce changes in carbon monoxide (CO) membrane conductance (DmCO) and capillary lung volume (Vc). Measurements were performed in 25 lowlanders at Brussels (D0), at 4,300 m after a 2- or 3-day exposure (D2,3) without preceding climbing, and 5 days later (D7,8), before and after an exercise test, under a trial with two arterial pulmonary vasodilators or a placebo. The nitric oxide (NO)/CO transfer method was used, assuming both infinite and finite values to the NO blood condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…The annual rate of decline in FEV1 in the present study was slightly greater (-90 mL in the placebo group and -123 mL in the doxycycline group) compared with that observed in the re-evaluation performed by our group (-73 mL in patients that received doxycycline) and with that identified in the study of TaveiraDaSilva and colleagues (-75 mL) [1,8]. Can we assign a greater decline in FEV 1 identified in the doxycycline group in the present study to a greater impairment in baseline pulmonary function?…”
Section: Tlno/tlco Ratio Is Not the End Of The Roadcontrasting
confidence: 46%
See 2 more Smart Citations
“…The annual rate of decline in FEV1 in the present study was slightly greater (-90 mL in the placebo group and -123 mL in the doxycycline group) compared with that observed in the re-evaluation performed by our group (-73 mL in patients that received doxycycline) and with that identified in the study of TaveiraDaSilva and colleagues (-75 mL) [1,8]. Can we assign a greater decline in FEV 1 identified in the doxycycline group in the present study to a greater impairment in baseline pulmonary function?…”
Section: Tlno/tlco Ratio Is Not the End Of The Roadcontrasting
confidence: 46%
“…It could be suggested that both conductances might be lower than these in vitro values; however, it seems highly unlikely that both in vitro values were overestimated, and no published hCO value is ,0.58 mmHg?min -1 in normoxia. Interestingly, using the aforementioned hNO/hCO leads to increased Dm [8], reaching the morphometric value of WEIBEL et al [10]. This reasoning has sharp consequences for the interpretation of both TLCO and TLNO as, if the hNO/hCO value of 7.7 is confirmed, it would lead us to consider that TLCO is mainly dependent on Vc, as TLNO would be equally dependent on Dm and Vc.…”
Section: Tlno/tlco Ratio Is Not the End Of The Roadmentioning
confidence: 78%
See 1 more Smart Citation
“…Subsequently, physiological studies, involving simultaneous nitric oxide (NO) and CO uptake, have shown that 80% of the resistance to CO transfer from alveolar gas to intracapillary Hb (∼1/T LCO .sb) lies in the red cell itself 17 18. Thus, it is not unreasonable to describe the T LCO as a ‘window on the pulmonary microcirculation’ 19…”
Section: –1957: Understanding the Physiology Of Co Uptakementioning
confidence: 99%
“…These two groups, from Cambridge, UK17 and Bordeaux, France,18 have since shown that, for NO, 35–40% only of the transfer resistance lies in the red cell (80% for CO). Thus, T LNO .sb is more weighted to the alveolar and capillary surface area, that is, true diffusion, than to the red cell.…”
Section: Tlno·sb the Futurementioning
confidence: 99%